Bradykinin and its role in osteoarthritis - L. De Falco; A. Fioravanti; M. Galeazzi; S. Tenti (PAGEPress Publications, 2013)
Osteoarthritis (OA), the most common joint disorder, is a disease involving all the articular structures. It presents both degenerative and inflammatory aspects. Recently, the important role of Bradykinin (BK), a phlogistic mediator, has been proposed in the pathophysiology of OA. In our review, we summarized the currently available information on the mechanisms of action of BK in OA by linking its B2 receptors. Then, we analyzed the data about the effects of BK in synoviocytes and chondrocytes cultures. Furthermore, we described the action of B2 receptor antagonists (Icatibant and Fasitibant), presenting them as new promising symptom-anddisease- modifying agents in the treatment of OA. However, more in vitro, animal model and clinical studies, are needed to better understand the mechanisms of action as well as the efficacy and tolerability of the B2 receptor antagonists in OA.